Assessing visual communication and content performance of mobile learning among internet users - Mat Sharif, Eizan Azira (2015)
The growth of mobile technologies and the accession of a new mobile network that is 4G or Forth Generation are deemed as a breakthrough to launch new tool in the pedagogical paradigm known as Mobile Learning. Mobile Learning or M-learning is a distance learning system that gives opportunity for the working adults as well as for those who wants to further their study. Mobile Learning is learning accomplished by the use of small, portable computing devices such as Smartphones and Tablets which help M-learners typically view content and/or lessons in small, manageable formats that can be applied when the laptop or fixed station computers are unavailable. Mobile Learning also an arsenal to support learners and teachers as they navigate the options available in the expanding world of distance learning (McConatha, 2007). Mobile Learning considered as a stride ahead of e-learning because of its features; fast and extensive, reaching away to the geographically wide-spread learners, even though they have no Internet connectivity. The purpose of this study is to assess visual communication and content performance of Mobile Learning and to identify the performance of 4G mobile network in Malaysia using of Smartphones and Tablets among mobile users. The study applied modified UTAUT (Unified Theory of Acceptance and Use of Technology) model introduced by Liu (2008) which consists of nine key constructs. The four key constructs which were performance expectancy, effort expectancy, social influence and facilitating conditions were based on the original UTAUT introduced by Venkatesth et al. (2003) while the five key constructs were presented by Liu (2008) were self efficacy, mobility, self management, perceived enjoyment and attainment values directly helped to identify the factors of Mobile Learning usage among internet users. The survey was conducted in Klang Valley area and applied a qualitative in-depth interview using phenomenology approach. The informants were interviewed until the data reaches the saturation point, and they were selected based on purposive and snowball sampling. Thirty informants involved in this study were based on a high and moderate mobile internet and internet users. NVivo 10 software was used to analyze the data and to create themes and categories, apart from using triangulation to ensure the reliability and validity of the study. There were constructive effects of Mobile Learning results. It appears that the future generations are extremely subject to use new technology as a matter of fact, they appear to embrace it. All of the informants were seemed to be amazed with collaboration between Mobile Learning and 4G mobile network; as an educational platform for users/learners which they uttered will be a good learning program. They were also expressed that it may be the learning future program for those who want to study, but yet do not have time to attend classes due to busy with works, attending late meetings and outstations. The results of the study show that the informants were satisfied with the visual communication and content performance of Mobile Learning as well as the 4G mobile network performance and recommended to execute Mobile Learning policies and program as soon as possible. Mobile Learning considered to be a new program that will continue to gain popularity in the future based on its convenience. With the development of social networking such as Facebook, Twitter, MySpace, Instagram and many others, blogging and YouTube, the users expect to be able to utilize mobile technology on the fly to connect anywhere and anytime of the daytime. The fact was that convenience is everything in today’s busy society and will remain to be in generations to occur. Generally, it can be concluded that Mobile Learning had received an encouraging outcomes from the informants. Further, it is suggested that more research need to be conducted in the future, focusing on different modes of devices such iPod and MP3.